Low-Power Millimeter Wave Transmitters for High Data Rate Applications - Khalaf, Khaled; Vidojkovic, Vojkan; Long, John R.; Wambacq, Piet.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses low power techniques for millimeter wave transmitter IC. Considerations for the front-end design are followed by several implementation examples in the 60GHz band in CMOS down to 28nm technology. Additionally, the design and implementation details of digitally-modulated millimeter wave polar transmitters are presented.
Introduction -- Design Considerations for High-Datarate Low-Power 60GHz TX Front-Ends -- 60GHz TX Front-Ends in Advanced CMOS Technologies with Improved Back-Off Efficiencies -- Digitally-Modulated Polar Transmitters in 40nm CMOS.
Keywords: Electronic circuits; Telecommunication; Electric power production; Electronic Circuits and Systems; Microwaves, RF Engineering and Optical Communications; Electrical Power Engineering